Scoping Literature Review: What Activities Can Help Students Discover Permutations? - Putra, Aan; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Laswadi, Laswadi; Nusantara, Duano Sapta (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2023)
Mathematical knowledge will be meaningful for students if it is discovered through mathematical rediscovery activities. This research aims to provide an overview of the activities carried out by researchers in teaching material on multiplication rule and permutation as an insight for other researchers to try various activities that are relevant for teaching combinatorics material in general. This research is a scoping literature review using the 8-stage framework of Xiao & Watson. The review was carried out on 6 relevant articles published in various reputable international journals without a specific time limit. Based on the results of the review, it was found that learning permutations using activities included using the context of towers, beaded bracelets, presentation sequences, teddy bears, and photography. The activities used generally consist of arranging physical objects. The author suggests using reorderable objects to teach permutations. The context used must be adapted to the knowledge and experience of the students.